Geotechnical and geoenvironmental engineering education during the pandemic. Issue 3 (7th May 2021) - Jiang, Ning-Jun; Hanson, James L; Della Vecchia, Gabriele; Zhu, Cheng; Yi, Yaolin; Arnepalli, Dali N; Courcelles, Benoit; He, Jia; Horpibulsuk, Suksun; Hoy, Menglim; Takahashi, Akihiro; Arulrajah, Arul; et al.
Abstract : This paper reports the impact of coronavirus disease 2019 on the practice and delivery of geotechnical and geoenvironmental engineering (GGE) education modules, including lectures, lab sessions, student assessments and research activities, based on the feedback from faculty members in 14 countries/regions around the world. Faculty members have since adopted a series of contingent measures to enhance teaching and learning experience during the pandemic, which includes facilitating active learning, exploring new teaching content related to public health, expanding e-learning resources, implementing more engaged and student-centred assessment and delivering high-impact integrated education and research. The key challenges that faculty members are facing appear to be how to maximise the flexibility of learning and meet physical distancing requirements without compromising learning outcomes, education equity and interpersonal interactions in the traditional face-to-face teaching. Despite the challenges imposed by the pandemic, this could also be a good opportunity for faculty members obliged to lecture, to rethink and revise the existing contents and approaches of professing GGE education. Three future opportunities namely, smart learning, flipped learning and interdisciplinary education, are identified. The changes could potentially provide students with a more resilient, engaged, interactive and technology-based learning environment.